Odpowiedzi

2010-03-16T18:30:17+01:00
-(x+3)+(2x-1)=(1+4x)+(3+x)
-x - 3 + 2x - 1= 1 + 4x + 3 + x
- 3 + 2x - 1= 1+ 4x + 3
- 4 -1 -3 = 4x - 2x
- 8 = 2x (zamiana stronami)
2x = - 8 | :2
x = - 4


-(x+3)-(2x+8)=(-3-2x)-(2x +1)
- x - 3 - 2x - 8 = -3 - 2x -2x -1
- 3x - 11 = - 4 - 4x
4x - 3x = 11 - 4
x = 7


(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3 - 2x - x - 4 -2x - 5 = 3x - 4 -5x - 7
3 - 5x - 5 - 4 = - 2x - 11
-5x + 2x = - 11 - 3 +9
- 3x = 5 | : (-3)
x = - 1 i 2/3


(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4 - x - 2x - 3 + x - 4 = - 2x + 3 -x -7
4 - 2 x - 7 = - 3x - 4
- 2x + 3x = 7
x= 7

(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x - 5 + x -7 - 2x + 8 = -3x + 4 -x +6
3x - 12 + 8 = - 4x + 10
3x + 4x = 10 +12 - 8
7x = 14 | :7
x = 2

-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
- 4 + 2x -2x -4 = 3x-1 +2x - 5 -7 + 3x
- 8 = 8x - 13
13 - 8 = 8x
8x = -5
x = - 5/8
Najlepsza Odpowiedź!
2010-03-16T18:44:19+01:00
-(x+3)+(2x-1)=(1+4x)+(3+x)
-x-3+2x-1=1+4x+3+x
-x+2x-4x-x=1+3+1+3
-4x=8/(-4)
x=(-2)

-(x+3)-(2x+8)=(-3-2x)-(2x +1)
-x-3-2x-8=-3-2x-2x-1
-x-2x+2x+2x=-3-1+3+8
x=7

(3-2x)-(x+4)-(2x+5)=(3x-4)-(5x+7)
3-2x-x-4-2x-5=3x-4-5x-7
-2x-x-2x-3x+5x=-4-7-3+4+5
-3x=-5/ (-3)
x=1 ²/₃

(4-x)-(2x+3)+(x-4)=-(2x-3)-(x+7)
4-x-2x-3+x-4=-2x+3-x-7
-x-2x+x+2x+x=-7-4+3+4
x=(-4)

(4x-5)+(x-7)-(2x-8)=(-3x+4)-(x-6)
4x-5+x-7-2x+8=-3x+4-x+6
4x+x-2x+3x+x=4+6+5+7-8
7x=14/7
x=2

-(4-2x)-(2x+4)=(3x-1)+(2x-5)-(7-3x)
-4+2x-2x-4=3x-1+2x-5-7+3x
2x-2x-3x-2x-3x=-1-7-5+4+4
-8x=-5/ (-8)
x=⁵/₈